A COMPARATIVE ANALYSIS ON CROSS CULTURAL MANAGEMENT: A CASE STUDY ON AFRICAN CULTURE IN BRUNEI DARUSSALAM - Liza Mariah Haji Azahari; Monica Lesley Anak Ason; Nurin Jazlina binti Awang Haji Damit; Muhammad Izzuddin bin Yahaya (Journal of Islamic, Social, Economics and Development, 2019)
This study is a case development which aim to examine the cross-cultural issues of expatriates working in Brunei Darussalam and its impact on certain areas of management such as communication and language, emotional expression, the gender roles and conflict management. An organisation that incorporates cross cultural management recruits more expatriates from diverse foreign countries. This organisation is then said to have cultural diversity which has certain effects on the work outcome and processes due to the existence of differences in background among staff. Culture diversity is important for some organization and used as comparative advantage. Two respondents from Nigeria and Sudan have contributed towards this study. Both expatriates are exposed to foreign culture that influence their adaptation which may penetrate changes in attitudes and behavior of expatriate. The findings show no significant differences in adjusting in Brunei cultures, although some of factors have been identified that enable them to adapt to culture in Brunei such as sharing same Islamic religion and they used their past experiences in Malaysia that help them to adapt to the local management culture. However, the prominent factor of cultural adaptation lies in language which facilitates the overall communication process and will lead to better cross cultural management.